1983
DOI: 10.1042/cs0640273
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Plasma Renin

Abstract: 1. The epidemiological characteristics of plasma renin activity (PRA) were established in 1999 members of occupational groups in North and West London. 2. The main finding was that PRA was inversely associated with systolic blood pressure in men, the percentage fall in PRA (on a log scale) being 8.4% for each increase of one standard deviation in systolic blood pressure. There was a less obvious inverse relationship in women. 3. However, blood pressure accounted for less than 1% of the variance in PRA. 4. Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
3
3

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(51 citation statements)
references
References 0 publications
2
43
3
3
Order By: Relevance
“…Some of these studies spanning a period of nearly 25 years are summarised in Table 1. As can be seen, on average PRA in blacks is about 50% to that in whites and the differences are similar for men and women, 15,16 however it is also relevant to note the wide variability indicating that the PRA in a substantial proportion of blacks is likely to be in Values are means ± s.d. (n); PRA activity (ng/ml/hr); supine and for subjects on their normal sodium intake.…”
Section: Comparison Of Pra Between Blacks and Whitesmentioning
confidence: 87%
“…Some of these studies spanning a period of nearly 25 years are summarised in Table 1. As can be seen, on average PRA in blacks is about 50% to that in whites and the differences are similar for men and women, 15,16 however it is also relevant to note the wide variability indicating that the PRA in a substantial proportion of blacks is likely to be in Values are means ± s.d. (n); PRA activity (ng/ml/hr); supine and for subjects on their normal sodium intake.…”
Section: Comparison Of Pra Between Blacks and Whitesmentioning
confidence: 87%
“…Observational studies in humans have demonstrated that patients with high levels of circulating renin are at increased risk for myocardial infarction and other atherosclerotic cardiovascular events. 1,[22][23][24][25]32 In addition, studies in several different models of atherosclerosis have shown that ACE inhibitors and angiotensin-type 1 receptor antagonists inhibit atherosclerotic lesion formation. 18 -21 The mechanism whereby angiotensin II-induced hypertension accelerates and worsens atherosclerosis is probably multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…18 -21 Finally, numerous studies in humans have shown that high renin forms of hypertension are particularly proatherogenic and that patients with high renin hypertension are at increased risk of myocardial infarction. [22][23][24][25] The recently presented results of the Heart Outcomes Prevention Evaluation (HOPE) trial demonstrated a remarkable decrease in cardiovascular morbidity and mortality when normotensive individuals at increased risk for cardiovascular events were treated with an ACE inhibitor. 26 Taken together, these data specifically implicate the reninangiotensin II system in the pathogenesis of atherosclerosis.…”
mentioning
confidence: 99%
“…The pharmacodynamic responses to these agents have been claimed to be directly related to plasma renin activity (Case et al, 1977), which falls with age (Meade et al, 1983 (Hockings et al, 1985). The pharmacokinetics of enalaprilat in these subjects is described in a separate paper (Hockings et al, 1986 Blood pressures and heart rate recordings were made at these times by means of a semi- Derkx et al, (1978).…”
Section: Introductionmentioning
confidence: 99%